Peace journalism in times of 'war risks': Coverage of the hydrocarbons conflict in Turkish Cypriot and Greek Cypriot newspapers - Ciftcioglu, Vasvi; Shaw, Ibrahim Seaga (Sage Publications Inc, 2021)
The Mediterranean island of Cyprus, the last divided country in Europe, faced a grave risk of plunging into war in September 2011. The reason behind this danger was represented as the confrontation over the excavation of hydrocarbon reserves found in the Eastern Mediterranean Sea. The main goal of this article is to explore the extent to which peace journalism was practiced, or not, by analysing the front-page stories of the prominent Turkish Cypriot and Greek Cypriot newspapers about this conflict. A review of peace journalism research reveals that researchers have mainly focused on war reporting. In order to address this deficit in peace journalism research, this article focuses on a case study where there was a risk for military confrontation. The combined sample drawn from six newspapers in the respective communities indicates a strong preference towards war journalism. As the analysis further shows, the newspapers from both sides failed to discuss peaceful solutions to the hydrocarbons conflict and they also failed to discuss the negative repercussions of a possible war related to the hydrocarbons conflict.
Keywords: Conflict reporting; Cyprus Problem; hydrocarbons conflict; peace journalism; reconciliation; war journalism